The effect of enalapril maleat in ischemia reperfusion injury: Possible role of membrane bound enzymes - (:unkn) unknown (My University, 2001)
The present study evaluates the protective effect of enalapril maleat on myocardial ischemia-reperfusion injury. Membrane bound enzymes; Na+K+/Mg2+ ATPase and Ca2+/Mg2+ ATPase are known to regulate the membrane integrity. We hypothesized that if we could protect the cell membrane in ischemia-reperfusion period, we might have a chance to augment contractility. Thirty-two Guinea pig hearts were studied in an isolated Krebs-Henseleit solution-perfused Langendorff cardiac model. In Group 1, control hearts (n = 8) were arrested with St. Thomas Cardioplegic Solution (STHCS) alone. In Group 2 (n = 8), animals were pretreated with oral enalapril maleat (0.2mg/kg/daily) for ten days and arrested with STHCS. In Group 3, (n = 8) the hearts were arrested with enalapril maleat- (1 μmol/L) added STHCS. In Group 4 (n = 8), the hearts were again pretreated with oral enalapril maleat for ten days and then reperfused with enalapril maleat-added Krebs-Henseleit solution. Hearts were subjected to normothermic global ischemia for 90 minutes and then were reperfused at 37°C. The study groups showed better recovery of left ventricular systolic function. In terms of biochemical determinations, best results were achieved at Group 4. The Na+K+ ATPase and Ca2+ ATPase levels were measured at 466.38 ± 5.99 to 545.23 ± 8.79, and 884.69 ± 9.13 to 1254.34 ± 1.56, respectively (p < 0.05). Based on these results, it can be concluded that enalapril maleat protects the membrane integrity and thus plays a role in restoring the contractility in ischemia-reperfusion injury.